1979
DOI: 10.1099/00207713-29-3-204
|View full text |Cite
|
Sign up to set email alerts
|

Deoxyribonucleic Acid Relatedness of Strains of Yellow-Pigmented, Group D Streptococci

Abstract: Deoxyribonucleic acid (DNA) homalogy was used to examine genetic relatedness among 25 yellow-pigmented strains of group D streptococci and to clarify the possible genetic relatedness of these strains to Streptococcus faecium and Streptococcus faecalis. In all cases, the DNA of the yellow-pigmented strains hybridized with the DNA of S. faecium and S. faecalis at a level of less than 25%. Based on median thermal dissociation temperatures (Tm's) and hybridization tests, the yellow-pigmented strains were divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 11 publications
0
32
0
Order By: Relevance
“…These values were calculated from melting temperatures of 84.2, 84.4, and 84.1"C, respectively. Other workers have reported similar values (12,16). The DNAs of all strains of enterococci were tested against the DNAs of the labeled American Type Culture Collection type strains of S .…”
Section: Resultsmentioning
confidence: 97%
“…These values were calculated from melting temperatures of 84.2, 84.4, and 84.1"C, respectively. Other workers have reported similar values (12,16). The DNAs of all strains of enterococci were tested against the DNAs of the labeled American Type Culture Collection type strains of S .…”
Section: Resultsmentioning
confidence: 97%
“…However, there have been reports in the literature concerning uncertainty in the classification of some species (see Bridge & Sneath, 1983;Jones, 1978;Mundt & Graham, 1968) and sub-species (Deibel, 1964;Jones et al, 1972). Studies using DNA composition (Farrow et al, 1983), DNA-DNA hybridization under optimal and stringent conditions (Bridge & Sneath, 1982;Farrow et al, 1983;Vaughan et al, 1979), rRNA-DNA hybridization (Garvie & Farrow, 198 1 ;Kilpper-Balz et al, 1982;Schleifer & Kilpper-Balz, 1984), lipid composition (Farrow & Collins, 1985), and analysis of isoprenoid quinones (Collins & Jones, 1979), have contributed to a better understanding of enterococcal species. Moreover, analysis of the penicillin-binding proteins (PBPs) in strains of Enterococcus faecalis and E. faecium showed that there were species-specific patterns of these cytoplasmic membraneassociated proteins (Williamson et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…enzymogenes Christensen and Cook 1978, the combination Lysobacter enzymogenes subsp. cookii Christensen 1978 (Christensen & Cook, 1978) and the combination Streptococcus casseliflavus (Mundt & Graham, 1968) Vaughan et al 1979(Mundt & Graham, 1968Vaughan et al, 1979) were in accordance with the wording of the 1975 and 1992 revisions of the International Code of Nomenclature of Bacteria (Lapage et al, 1975(Lapage et al, , 1992 and that according to Rule 24a, Note 1 from the 1975 revision:…”
mentioning
confidence: 98%
“…enzymogenes Christensen and Cook 1978, the combination Lysobacter enzymogenes subsp. cookii Christensen 1978 and the combination Streptococcus casseliflavus (Mundt & Graham, 1968) Vaughan et al 1979 were not included on the Approved Lists of Bacterial Names (Skerman et al, 1980(Skerman et al, , 1989, are not to be added and are, therefore, not validly published.…”
Section: At Its Meetings In 2008 At the Iums Bacteriology And Appliedmentioning
confidence: 99%
See 1 more Smart Citation